2011
DOI: 10.1007/s00253-011-3210-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and application of a different glucose uptake system that functions as an alternative to the phosphotransferase system in Corynebacterium glutamicum

Abstract: Corynebacterium glutamicum uses the phosphoenolpyruvate-dependent sugar phosphotransferase system (PTS) to uptake and phosphorylate glucose; no other route has yet been identified. Disruption of the ptsH gene in wild-type C. glutamicum resulted, as expected, in a phenotype exhibiting little growth on any of the PTS-sugars: glucose, fructose, and sucrose.However, a suppressor mutant that grew on glucose but not on the other two sugars was spontaneously isolated from the PTS-negative strain WTΔptsH. The suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 18 publications
3
51
0
Order By: Relevance
“…1), unlike the wild-type strain, exhibited a phenotype of resistance to 2-deoxyglucose, which is known to be a toxic substrate for the glucose-PTS of this organism (Mori and Shiio 1987), we predicted that the suppressor strain would utilize glucose via a different system involving a particular permease and the native glucokinases. Our analysis following these observations eventually led to the finding that two myo-inositol transporters encoded by iolT1 (Cgl0181, NCgl0178) and iolT2 (Cgl3058, NCgl2953) mediate glucose uptake in this organism and that glucose phosphorylation depends on glucokinase activity (Ikeda 2012;Ikeda et al 2011). We also showed that inactivation of iolR, a putative transcriptional regulator gene, enables strain WTΔptsH to grow on glucose through the derepression of iolT1, as was the case with the suppressor strain SPH2.…”
Section: Introductionmentioning
confidence: 73%
See 4 more Smart Citations
“…1), unlike the wild-type strain, exhibited a phenotype of resistance to 2-deoxyglucose, which is known to be a toxic substrate for the glucose-PTS of this organism (Mori and Shiio 1987), we predicted that the suppressor strain would utilize glucose via a different system involving a particular permease and the native glucokinases. Our analysis following these observations eventually led to the finding that two myo-inositol transporters encoded by iolT1 (Cgl0181, NCgl0178) and iolT2 (Cgl3058, NCgl2953) mediate glucose uptake in this organism and that glucose phosphorylation depends on glucokinase activity (Ikeda 2012;Ikeda et al 2011). We also showed that inactivation of iolR, a putative transcriptional regulator gene, enables strain WTΔptsH to grow on glucose through the derepression of iolT1, as was the case with the suppressor strain SPH2.…”
Section: Introductionmentioning
confidence: 73%
“…In our previous report (Ikeda et al 2011), we showed that the myo-inositol transporters IolT1 and IolT2 function as alternatives to the glucose-PTS in C. glutamicum. In this study, we identified a third glucose uptake bypass as the bglF-specified EII component of the β-glucoside-PTS in C. glutamicum ATCC 31833.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations